Discourses of Muslim-Friendly Tourism (Indonesia Empirical Cases) - Febrina Mahliza; Lucky Nugroho; Yananto Mihadi Putra; Erik Nugraha; Wiwin Sukiati (Journal of Islamic Economics and Social Science (JIESS), 2021)
The tourism sector in the period before the Covid-19 Pandemic contributed significantly to the country's revenues. In addition, as a country with the largest Muslim population in the world, Indonesia has the potential to develop Muslim-friendly tourism. Furthermore, the Indonesian government plans to make Indonesia the center of the world's Islamic economic and financial ecosystem. Therefore, this conceptual paper aims to know the concepts and services of Muslim-friendly tourism in Indonesia. The methods used using qualitative methods derived from research and scientific articles related to research questions are as follows: (i) i) How is the concept of Muslim-friendly tourism?; (ii) How to tour Muslim-friendly services?. The result of this conceptual paper is the concept of Muslim-friendly tourism and its implementation strategy. The implication of this research is to provide scientific characteristics both for academics and practitioners in tourism